Study of the mechanism of photocatalytic activity of zinc oxide in the presence of synthetic zeolite - V. I. Loganina; A. D. Ryzhov; I. A. Pronin; A. A. Karmanov; N. D. Yakushova (Vestnik MGSU)
Introduction. The regularities of changes in the photocatalytic activity of zinc oxide ZnO in the presence of synthetic zeolite are investigated. The data on the photocatalytic properties of the surface of lime coating based on the composition with the addition of zinc oxide and synthetic zeolite are presented.Materials and methods. A complex of general scientific research methods was used. Lime with activity of 83 % was used in the development of the formulation of the finishing composition. An aluminosilicate additive was used as a synthetic zeolite, obtained by adding microdispersed aluminum powders to sodium liquid glass with silicate module of 2.9 at a temperature of 60 °C for 90 minutes. The photocatalytic activity of ZnO using synthetic zeolite was studied by photodegradation of methylene blue dye under the action of UV light. The methods presented in the scientific and technical literature were used. Spectroscopic studies of the specimens were carried out on an FSM 1201 IR Fourier spectrometer (LLC “Infraspek”, Russia) and an SF-56 spectrophotometer.Results. An increase in the photocatalytic properties of the surface of a lime coating based on a composition using ZnO oxide and synthetic zeolite was established. The optical band gap of ZnO was determined. It was revealed that the optical band gap of zinc oxide in combination with synthetic zeolite is 2.96 and 2.70 eV, which is significantly less than the value of 3.37 eV characteristic of zinc oxide.Conclusions. To impart self-cleaning properties to lime coatings, it is proposed to introduce zinc oxide into the formulation of the photocatalyst together with an additive based on synthetic zeolite.